Evaluation of Tsanawiyah Madrasah Curriculum Policy After K 13 - Novita Sari; Syafaruddin Syafaruddin; Khairunnisa Khairunnisa (EDUTEC : Journal of Education And Technology, 2021)
The purpose of this research is 1. For curriculum planning 13 at MTS Negeri Lubuk Pakam 2. For the implementation / implementation of the curriculum in MTS Negeri Lubuk Pakam 3. For the evaluation of post-13 kurikulm policy. This type of research is field research, while the research approach used is qualitative approach. The results of this study are: 1. Planning of the learning curriculum of Madrasah Tsanawiyah al-washliyah Labu Beach is arranged by paying attention to things such as formulating in the form of units of time needed by teachers such as teacher training to solidify the transition of curriculum to K13. Prepare learning programs through a face-to-face system of structured assignments, unstructured Independent activities then self-development activities. 2. The implementation of the K13 curriculum, especially in MTS al-washliyah Pantai Labu, is to use a package system that is regulated that the lesson hours for each subject in the package system are allocated as stated in the curriculum structure of the time allocation arrangement for each subject contained in odd and even semesters in one year of study. The learning burden set out in this provision is the burden of learning package system at the secondary education level. The package system is a system of organizing educational programs whose learners are required to follow all learning programs and learning burdens that have been set for each class in accordance with the curriculum structure that applies to the learning load education unit of each subject in the package system expressed in units of lesson hours. 3. Evaluation of post-K13 curriculum policy by creating an evaluation team that one of its teams has PKM Curriculum within 2 weeks